Analysis of WWER-1000 Fuel Deformation Using the Refueling Machine Control System - A. A. Lapkis; A. N. Bezmateva; E. A. Abidova (Глобальная ядерная безопасность)
The analysis of the geometric dimensions of fuel assemblies, whose change may lead to mashing of the cassettes in the core, is performed at this stage only after removing the fuel assemblies from the reactor. This paper considers the possibility of analyzing the mashing of WWER-1000 cassettes using the control system of the reloading machine. Based on data from an industrial experiment at the Rostov NPP, a typical distribution of friction forces over the height of the WWER-1000 reactor core is assessed.